Preparation and characterization of activated carbon - Badri, M.; Crouse, Karen A. (1990)

(untitled)
This paper summarizes the work on the preparation and characterization of activated carbon at the University of Agriculture Malaysia. The preparation involved heating an agricultural by-product such as coconut shells and palm oil kernal shells in vacuum. Studies on the physical properties of the carbon thus prepared are also reported. These include the estimation of impurities, identification of functional groups, measurement of conductivity and adsorption and determination of the catalytic effect of carbon in a chemical reaction.